El homicidio preterintencional - Ribas, Eduardo Ramón (Revista de Derecho Penal y Criminología, 2019)
El hecho base que encierra el término homicidio preterintencional tiene dos dimensiones: una dolosa, pues el sujeto pretende causar unas lesiones, y otra imprudente, integrada por un resultado no deseado, la muerte. Aunque habitualmente se ha resuelto, en los últimos años, apreciando un concurso ideal entre un delito de lesiones dolosas, consumadas o intentadas, y un delito de homicidio imprudente, la progresiva ampliación jurisprudencial del concepto de dolo deja casi sin margen de aplicación dicha solución, sustituida por la de homicidio doloso. There is a form of manslaughter in which a difference can be made between two elements or dimensions. On the one hand, there is the intentional action on the part of the subject who aims and achieves the injury of another person. On the other hand, there is the negligent act of unwillingly killing such a person as a result of former intentional act. Courts and scholars, applying the concurrency norms, have considered the subject of such an action as responsible for both the intentional injuries and the manslaughter. However, due to the progressive enlargement of the concept of criminal intent such solution has become unviable. Latest voices have looked on the intentional homicide as the best and only legal answer for cases of this kind.